Tanggung Gugat Apabila Terjadi Kecelakaan Sebab Polisi Tidur - Michael, Tomy; Faruq, Umar (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
This article is intended to address the issue of community accountability in the event of an accident due to speed limitation or 'polisi tidur’. The method used is normative legal research, which uses a statutory approach and a conceptual approach. This article concludes that the public can sue the Minister of Public Works or State Legal Entity under the Department of Transportation. In the daily life of the village apparatus to always supervise the surrounding community to avoid fatal legal actions. Communities should be given directions by village officials in accordance with the legislation in Indonesia.